The Effect of Group Tutoring to Reduce Student Bullying Behavior - Desri Jumiarti; Arifan Fadila; Dasril Dasril; Rina Yulitri (Journal of Islamic Education Students (JIES), 2023)
This research aims to assess the positive impact of implementing group counseling in reducing bullying behavior. The research method employed is quantitative with an experimental design, using a Pre-experimental design with a one-group pre-test post-test design type. The study population includes all eighth-grade students, with a sample of 10 students selected through purposive sampling. The instrument used is a Likert-scale bullying behavior questionnaire. Data analysis yields a calculated t-value greater than the critical t-value, indicating that the alternative hypothesis (Ha) proposing a significant influence of group counseling services on bullying behavior is accepted, while the null hypothesis (H0) suggesting no significant impact is rejected. Group counseling has proven to have a significant effect in reducing bullying behavior among students, as evidenced by the comparison of pretest and posttest scores. The findings of this research contribute significantly to the development of group counseling intervention strategies to address bullying behavior within the school environment.